The meaning of merit: talent versus hard work legitimacy - Friedman, S; Ellersgaard, C; Reeves, A; Larsen, AG (Oxford University Press, 2023)
Elites often use merit to explain, justify, and make sense of their advantaged positions. But what exactly do they mean by this? In this paper, we draw on 71 interviews with elites in Denmark and the UK to compare self-justifications of meritocratic legitimacy. Our results indicate that while elites in both countries are united by a common concern to frame their merits as spontaneously recognized by others (rather than strategically promoted by themselves), the package of attributes they foreground vary significantly. In the UK, elites tend to be "talent meritocrats"who foreground their unique capacity for ideational creativity or risk taking, innately good judgment, and "natural"aptitude, intelligence, or academic ability. In contrast, in Denmark, elites are more likely to be "hard work meritocrats"who emphasize their unusual work ethic, extensive experience (as a signal of accumulated hard work), and contributions outside of work, particularly in civil society. We tentatively argue that one explanation for this cross-national variation is the role that different channels of elite recruitment play in amplifying legitimate notions of merit. In the UK, for example, elite private schools act to nurture ideas of exceptionalism and natural talent, whereas in Denmark elite employers socialize the connection between hard work and success. These findings suggest that nationally specific understandings of merit can have quite different implications for the legitimation of inequality.